EKSPLORASI ASUHAN KEPERAWATAN KELUARGA DI RUMAH (HOME CARE) DI PUSKESMAS SUDIANG RAYA - Kadrianti, Erna; Hasifah, Hasifah (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
There are still quite a lot of health problems in the world and in Indonesia that require long-term care at home. Home care is a form of nursing service, including community nursing care carried out at home. This research aims to explore family nursing care through home visits (Home Care) at the Sudiang Raya Community Health Center, with the main focus being policies, objectives, competencies possessed by implementers, implementation processes, monitoring and evaluation of the implementation of family nursing care through home visits (Home Care). This research took place at the Sudiang Raya Community Health Center, Makassar City. The research was carried out March – August 2022. This research uses descriptive qualitative methods to understand and explain the phenomenon of implementing nursing care through home visits. Data collection used an in-depth interview guide for 6 nurse participants who worked at the Community Health Center. The data collected was in menuscript form and then analyzed using Cresswell to determine themes. The themes in this research are 1) the role of community nurses, 2) Implementing Family Nursing Care, 3) Preventive and curative services, and 4) Home Care in the Community.